Relationship with Leadership Style Burnout Syndrome and Nursing Performance in patients of RSUD Bajawa - Due, Maximus Bertolomeus; Nursalam, Nursalam; Setiya Wahyudi, Andri (Universitas Airlangga, 2020)
Introduction: Leadership Style was a set of behavioral patterns and strategies that were often used by leaders to influence subordinates to achieve organizational goals. The leadership style was closely related to burnout syndrome and nurse performance. The purpose of this study was to determine the relationship of leadership style with burnout syndrome and the performance of nurses in the inpatient room of Bajawa District Hospital.Method: The design of this study was cross-sectional. The population in this study was 113 and a sample of 104 respondents was obtained with total sampling. The independent variable was the leadership style. The dependent variable is burnout syndrome and nurse performance. The instrument uses a questionnaire. Data were analyzed with Spearman's Rho.Results: There was a relationship between leadership style with emotional exhaustion (p = 0,000), leadership style with depersonalization (p = 0,000), leadership style with decreased self-achievement (p = 0,000) leadership style with nurse performance (p = 0.002).Conclusion: The application of a positive leadership style will reduce the incidence of burnout syndrome and improve nurse performance. So that nurse leaders need to be equipped with effective leadership skills.